Pengaruh Hubungan Keterlibatan Orang Tua terhadap Prestasi Belajar Siswa Dalam Pendidikan Agama Islam pada siswa kelas VIII SMPN 5 Bangka - Agus Yasin; Chevira Yasmin Putri Indriyanti; Nini Karnila Oktavia; Siti Fadilah (At Turots: Jurnal Pendidikan Islam, 2024)
The involvement of parents at the stage of child development is something that greatly influences the results of their growth and development, especially when children are teenagers, parents are still the first teachers for their children, even though there is already a teacher who can represent them in conveying all learning material. parents still have a large share in influencing the results of their children's learning achievements, and in a learning process, there are 3 interrelated elements namely, parents, students, and teachers. if one of them is not there then it is certain that there will be inappropriate learning outcomes so that it can be ascertained that parental involvement has a large contribution in increasing the results of learning achievement in each student, this study aims to determine the extent of the relationship between parental involvement in improving learning achievement in Islamic religious education for VIII students of SMPN 5 Mendo Barat, Bangka district. The research method used is quantitative research, with two variables, namely parental involvement (x), and student achievement in PAI (y). Data collection techniques were carried out through questionnaires, interviews, and documentation which were analyzed using prerequisite tests and simple linear regression tests. and the results of the study show that the significance value is 0.006. Because 0.006 <0.05, then H0 is rejected and Ha is accepted, so it can be stated that there is a significant influence between parental involvement on student achievement